Evaluation of the Effect of Concurrent Chronic Total Occlusion and Successful Staged Revascularization on Long-Term Mortality in Patients with ST-Elevation Myocardial Infarction. (10th February 2014) - Shi, Guoxiang; He, Pengcheng; Liu, Yuanhui; Lin, Yaowang; Yang, Xing; Chen, Jiyuan; Zhou, Yingling; Tan, Ning
Abstract : Aims . To investigate the impact of chronic total occlusion (CTO) in non-infarct-related artery (IRA) on the long-term prognosis and evaluate the clinical significance of staged revascularization in patients with ST-segment elevation myocardial infarction (STEMI). Methods . 1266 STEMI patients with primary percutaneous coronary intervention (PCI) were categorized as single-vessel disease (SVD), multivessel disease (MVD) without and with CTO. We study the clinical outcomes of patients after primary PCI in the following 3 years. Additionally, patients with CTO received staged revascularization, and major adverse cardiac events (MACE) during 3-year follow-up were recorded. Results . Presence of CTO was a predictor of both early mortality [hazard ratio (HR) 3.4, 95% confidence interval (CI) 2.4–4.5, P < 0.01 ] and late mortality (HR 1.9, 95% CI 1.4–3.6, P < 0.01 ), whereas MVD without CTO was only a predictor of early mortality (HR 1.7, 95% CI 1.3–2.3, P < 0.05 ). In CTO group, 100 patients had successful CTO recanalization, and 48 patients failed. During 3-year follow-up, patients with failed procedure had higher cardiac mortality (22.9% versus 9.0%, P = 0.020 ) and lower MACE-free survival (50.0% versus 72.0%, P = 0.009 ) compared to patients with successful procedure. Conclusion . The presence of CTO and not MVD alone is associated with long-term mortality. Successful revascularization of CTO in the non-IRA is associated with improved clinical outcomes in patients with STEMI undergoing primary PCI.